Concerns about Wild Dog (Cuon alpinus) Predation on Livestock in the Fringes of Aralam Wildlife Sanctuary, Kannur, Kerala - Roshnath, R.; Sethu, D.; Gokul, D.; Arjun, C. P. (Indian Forester, 2017)
Human-wildlife conflict is a serious obstacle for wildlife conservation. With the increase in human encroachments and decreasing natural habitat, negative interactions between humans and wild animals are intensified. This communication focuses on the incidence of Wild Dogs (Cuon alpinus) predation on livestock in Aralam and perspectives of the victims who lost their livestock, based on a questionnaire survey. Nineteen goats were killed by wild dogs between Feb-June (2015) in the fringe areas of Aralam Wildlife Sanctuary. Different reasons were suggested by the respondents for the sudden predation by wild dogs, which were not been reported earlier in the area. Even though compensations were provided by Forest Department for the losses caused by wild dogs, spreading of improper interpretation had concerned the people. Of the different mitigation measures suggested, well-maintained electric fencing could reduce the conflict to a greater extent.